DOES AFFECTIVE COMMITMENT MEDIATE THE IMPACT OF WORK-LIFE BALANCE AND JOB SATISFACTION ON TURNOVER INTENTION IN THE ACCOUNTING PROFESSION? - Asriningrum, Amalia; Pulungan, Andrey Hasiholan; Hasibuan, Ahmad Basid (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The high turnover rate of professional accountants has become a major concern for industries since it may expose companies' income. Understanding possible factors that may affect professional accountants' decisions to leave organizations may help companies to develop better retention strategies. By applying the Social Exchange and Organizational Commitment Theories, this study examines the effect of work-life balance and job satisfaction on turnover intention, with affective commitment as a mediating variable in the accounting profession in Indonesia. This study uses a quantitative approach. The selection of respondents used a purposive sampling method where data collection was carried out online from March to May 2025, through a questionnaire to 280 accountants and auditors. Of these, 197 responses (70.4%) were usable for analysis using SMART PLS 4.1.1.2. The results partially support our hypotheses. Work-life balance is the only factor that has a direct negative effect on turnover intention, while affective commitment mediates only the relationship between job satisfaction and turnover intention. This study contributes to practice so companies can develop appropriate strategies to retain accountants/auditors. As for the contribution to the literature, this study highlights the mediating role of affective commitment in turnover intention in the accounting profession.